THE CONSCIOUSNESS IN TERM OF LEVEL OF KNOWLEDGE AND IMPLEMENTATION AMONG DEVELOPER ON THE CURRENT SUSTAINABLE CONSTRUCTION PRACTICE IN MALAYSIA - Sitti Diana, Tamjehi; Afzan, Ahmad Zaini; Nadia, Zaini; Abdul Wafi, Razali; Nurfadilah, Darmansah (Construction Research Institute of Malaysia (CREAM), 2020)
In Malaysia, sustainable construction concept has been practiced by government since year 2000 to minimize the environmental issues in construction industry. The level of sustainability in construction industry is still low and need to be improved in which it requires responsibility by construction stakeholders particularly developers, who plays the important roles in the development process. This research adopted quantitative and qualitative research methodology to achieve the aim of the research. This research employed questionnaire survey to 142 developers and semi-structured interview to six (6) registered architects from Klang, Selangor to determine the level of consciousness in terms of knowledge and implementation level on the current sustainable construction practice in Malaysia. All selected developers were registered under Jabatan Perumahan Negara. The item studied include background of respondents, developer knowledge and the company implementation on sustainable construction practice. The findings from the questionnaire survey were analysed based descriptive and content analysis. The results indicate that the conceptual knowledge of developer on sustainable construction is at moderate level whereas the social concept is the highest compared to the economy and environment concept. The implementation of the developer on sustainable construction result is also at moderate level. From the research, it can be concluded that the consciousness in term of level of knowledge and implementation among developer on the current sustainable construction practice in Malaysia is still low. However, there is still room for improvement in terms of long-term benefits. Future research may focus on innovation strategy that can give more idea to improve the developer knowledge and better implementation on sustainable construction.